Samoocena usposobljenosti medicinskih sester za zdravstveno oskrbo pacientov v akutnih situacijah - Černe, Tanita Kaja (Obzornik zdravstvene nege, 2023)
Introduction: Novice nurses are often expected to perform at the same level of competence as those who are more experienced. The aim of this study was to explore the difference in the care of patients in acute treatment between the self-assessed competence of novice nurses and those employed for more than one year.Methods: A descriptive non-experimental quantitative method was employed. Using an online questionnaire, we conducted a survey on a random sample of 98 individuals employed in nursing. We gathered data on the basis of a questionnaire "Perception to Care in Acute Situations". The data were analyzed using descriptive statistics, the Mann Whitney U-test and the Kruskal Wallisov H-test. The level of statistical characteristics considered was < 0.05.Results: A poorer perception of care in acute situations of novice nurses compared to those employed for more than one year (U=271.000, p < 0.001) was demonstrated. Furtheremore, the difference between self-assessment of the competence of nurses with little experience in acute situations and those with much experience (U=293.000, p < 0.001) was identified. Discussion and conclusion: Novice nurses do not feel capable of working independently in acute situations. It was found that gender, age, field of work and previous experience with acute situations impact the nurses' self-assessment regarding competence. Future research should focus on the type of challenges that newly recruited nurses face and the importance of mentoring in nursing.
Keywords: medicinske sestre novinke; mentoring; mentorstvo; novice nurses; nursing; profesionalne kompetence; professional competence; samoocena; self-assessment; zdravstvena nega